Childbearing and women's survival: new evidence from rural Bangladesh - Menken, J.; Duffy, L.; Kuhn, R.
tbls.
pp. 405-426
Keywords: Nacimientos; Fecundidad; Sociedad; Población; Mujeres; Maternidad; Zonas Rurales; Mortalidad Materna; Bangladesh; Siglo XX